Management opinion about older workers in the organizational contexto (Research, Society and Development, 2021)
Objetive: To identify the opinion of managers about older workers in the organizational context. Method: Cross-sectional study with a quantitative approach, carried out with 176 managers from a public institution. The data were analyzed using descriptive statistics, prevalence ratio, confidence interval and p-value. Results: Female managers considered the aging of the workforce as a problem (PR = 0.872 / CI = 0.788-0.967 / p = 0.009). The older managers stated that the increase in the average age of the workforce would impact the organizational image (PR = 0.888 / CI = 0.801-0.985 / p = 0.024). The youth responded that the impact would be absenteeism (PR = 1.148 / CI = 1.045-1.261 / p = 0.004). The favorable characteristics present in workers, in the view of managers, are productivity, social skills, reliability and loyalty. Conclusion: Diversified and discordant perceptions of managers about older workers were evidenced. Despite recognizing the positive characteristics, managers still relate aging to problems, increased conflicts and changes in the institution's knowledge base.